2018
DOI: 10.3892/ol.2018.9424
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide induces the apoptosis and decreases NF‑κB expression in lymphoma cell lines

Abstract: Lymphoma is a type of cancer that develops from certain immune system cells. Arsenic trioxide (ATO) has attracted wide attention owing to its antitumor activities. However, the role of ATO in tumorigenesis and progression remains to be investigated. In the present study, the antitumor function of ATO was investigated in in lymphoma Raji and Jurkat cell lines and the effect of ATO on nuclear factor (NF)-κB expression levels. A Cell Counting kit-8 assay was used to assess cellular proliferation and the degree of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…However, UDCA promoted activity of SOD, CAT and GSH-Px and inhibited levels of MDA, ROS to the best level in hepatocytes, but it was still slightly lower than the Control. Nrf2 knockdown partially abrogated those effect (Zhong et al, 2018). Additionally, we revealed that UDCA promoted the nuclear translocation of Nrf2 and increased the levels of HO-1, NQO-1 in hepatocytes both in vivo and vitro, accompanied by a reduction of As(III)-provoked oxidative stress and subsequent hepatotoxicity.…”
Section: Discussionmentioning
confidence: 72%
“…However, UDCA promoted activity of SOD, CAT and GSH-Px and inhibited levels of MDA, ROS to the best level in hepatocytes, but it was still slightly lower than the Control. Nrf2 knockdown partially abrogated those effect (Zhong et al, 2018). Additionally, we revealed that UDCA promoted the nuclear translocation of Nrf2 and increased the levels of HO-1, NQO-1 in hepatocytes both in vivo and vitro, accompanied by a reduction of As(III)-provoked oxidative stress and subsequent hepatotoxicity.…”
Section: Discussionmentioning
confidence: 72%
“…ATO is a chemotherapeutic agent of idiopathic function used to treat leukemia that is unresponsive to first-line agents. It is suspected that ATO induces cancer cells to undergo apoptosis (11). In the current study, DrugBank and STITCH tools were used to identify the target genes of ATO.…”
Section: Resultsmentioning
confidence: 99%
“…Combined treatment with retinoic acid (RA) and ATO has been demonstrated to be curative for the majority of patients with APL (79). Furthermore, an increasing number of studies have proven the anti-carcinogenic properties of ATO in different tumors, including in gastric cancer (10), lymphoma (11), bladder cancer (12), head and neck cancer (13), and ovarian cancer (14). Although it has been reported that ATO may inhibit the progression of pancreatic cancer (15), the potential targets and molecular mechanisms of action of ATO remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have confirmed anti‐inflammatory effects of ATO on leukemia cells through the regulation of pro‐inflammatory factors (Binet & Girard, 2008; Dunoyer‐Geindre et al, 2017; Sharifizadeh et al, 2016; Zhong et al, 2018). Tissue factor (TF) also called platelet tissue factor, factor III, or CD142 which is involved in the clotting process, is highly expressed on the surface of leukocytes in APL.…”
Section: Immunologic Effects Of Ato On Apl and Other Leukemia Cellsmentioning
confidence: 92%
“…Also, ATO inhibits the expression and activity of NF‐ k B within the inhibition of IKK‐mediated I k B phosphorylation. Furthermore, IL‐6, as a protein involved in the proliferation of myeloid cells is suppressed by ATO (Sharifizadeh et al, 2016; Zhong et al, 2018). It has been reported that the enhancement of migration, adhesion, phagocytosis, and degranulation of secretory granules are a result of p38 and/or JNK activation in neutrophils undergoing treatment with ATO.…”
Section: Immunologic Effects Of Ato On Apl and Other Leukemia Cellsmentioning
confidence: 99%